Avaliação e caracterização de lignina em biomassa de Citrus sinensis L. Osberck - Porto, Deyvid de Souza (2017)
The large production of citrus residue has promoted problems in its processing and cultivation, resulting in biomass storage and environment pollution. It is estimated that 94 million tons of citrus are produced worldwide and 15.6 million residues are generated per year. Brazil has an important participation, due to the country is a world leader in the production of fruit and orange juice. Citrus biomass presents an extensive chemical diversity such as pectin, d-limonene, flavonoids and lignin, being an interesting object of study. Structural polymer present in the plant cell wall, the lignin has been used in phenolic resins, bioplastics and nanoencapsulation, for example. The fact that lignin presents as a valuable renewable raw material for the Brazilian chemical industry, the large amount of stored orange wood and the scarce literature about lignin in Citrus sinenses motived the present study. The study consisted in extracting lignin from stem, central root and secondary root from orange tree, using the TAPPI standard method, characterize lignin by Infrared (IR), Nuclear Magnetic Resonance (NMR), Elemental Analysis and Termical Analysis. The lignin contents for extractive-free orange samples were 19.80 % in the stem, 21.74% in the central root, 19.39% in the secondary root and 1,13% in the orange bagasse. The greatest amount of lignin in the orange tree was found in central root, responsible for the support of the structure of the plant, following the secondary root and the stem. The lignins from the different portions of the orange tree wood extraction by TAPPI T264 cm-97, presented low solubility in organic solvents, due to their compaction and folding that was confirmed by 13CNMR in solid state, DSC and TGA. The IR and NMR confirmed the characteristic lignin bands and the siryngil (1326 and 1115 cm-1) and guiacyl (1220 cm-1) monomers, which are found in hardwood type. Holocellulose contents found for samples of Orange bagasse (70.10%), stem (77.82%), central root (78.86) and secondary root (76.66%) extractive-free presented the expected content. The lignins from stem, central and secondary roots of orange tree wood obtained by alkaline pulping were soluble in organic solvent, as well as characteristic lignin signals for IV and NMR. The average yield between 20-24%, the solubility and the characteristics found in the MEV analysis of lignins obtained by alkaline pulping, are of interest for aplication these polymer in the encapsulation of substances and in Thermosets Composite.